2020
DOI: 10.1177/1350650120975518
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a comprehensive non-toxic, biodegradable and sustainable cutting fluid developed from coconut oil

Abstract: The evolution in development of cutting fluid from petroleum based products have brought about remarkable changes to the present and growing machining industry. Most of the cutting fluids are made of mineral base oils which are toxic, non-biodegradable and unsustainable. A major issue lies in their inappropriate disposal which results in surface water and groundwater contamination and consequently, agricultural products and food contamination. Hence, the objective of this study is to develop an alternative, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Another research for drilling was carried out using Coconut oil-based green cutting fluid, and its performance was compared with the Commercial cutting fluid [102]. Concentrated green cutting fluid was prepared using non-toxic emulsifiers (40%), natural additives (20%) and pure Coconut oil (40%).…”
Section: Edible Vegetable Oils As Cutting Fluids For Drilling Operationmentioning
confidence: 99%
“…Another research for drilling was carried out using Coconut oil-based green cutting fluid, and its performance was compared with the Commercial cutting fluid [102]. Concentrated green cutting fluid was prepared using non-toxic emulsifiers (40%), natural additives (20%) and pure Coconut oil (40%).…”
Section: Edible Vegetable Oils As Cutting Fluids For Drilling Operationmentioning
confidence: 99%
“…Spasiano et al (2020) explored the wastewater treatment of failed emulsions of bio-based lubrication and commercial synthetic cutting oil emulsions to achieve direct discharge of waste fluids, and the results showed that the new metalworking bio-based oils are simple to handle. Suvin et al (2020) developed a biodegradable emulsifier cutting fluid using coconut oil as an additive, and their drilling experiments showed that the performance of the cutting fluid was not significantly different from that of commercial emulsifiers, as well as being environmentally friendly and sustainable. The cooling effect of water-based cutting fluid is highly effective, as the water temperature does not exceed 100°C and takes away some of the heat when it evaporates at high temperatures (Najiha and Rahman, 2016).…”
Section: Introductionmentioning
confidence: 99%